2017
DOI: 10.4103/ijpsym.ijpsym_441_16
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry as an Economically Better Model for Reaching the Unreached: A Retrospective Report from South India

Abstract: Aim:In a resource-poor country such as India, telepsychiatry could be an economical method to expand health-care services. This study was planned to compare the costing and feasibility of three different service delivery models. The end user was a state-funded long-stay Rehabilitation Center (RC) for the homeless.Methodology:Model A comprised patients going to a tertiary care center for clinical care, Model B was community outreach service, and Model C comprised telepsychiatry services. The costing included ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…[1617] A recent retrospective study from India also found that telepsychiatry is an economically better model than regular outpatient model providing services to unreached special populations. [20]…”
Section: Discussionmentioning
confidence: 99%
“…[1617] A recent retrospective study from India also found that telepsychiatry is an economically better model than regular outpatient model providing services to unreached special populations. [20]…”
Section: Discussionmentioning
confidence: 99%
“… 37 In a study in India, the telepsychiatry services delivered from a tertiary psychiatric center to a distant primary healthcare center has shown to be very cost-effective than conventional in-person care. 38 …”
Section: Benefits Of Telepsychiatrymentioning
confidence: 99%
“…The challenges cited were: connectivity disturbances/failure, lack of workforce to allocate telepsychiatry responsibility, cost-effectiveness, maintaining confidentiality, and data security. 14 …”
Section: Review Of Telepsychiatry Models In the Countrymentioning
confidence: 99%